Preparation of maltodextrin stabilized α-tocopherol nanoemulsions using solvent-displacement technique - Firoozy, Mitra (Food science and technology international = Ciencia y tecnologia de los alimentos internacional, 2019)
α-Tocopherol nanoemulsions were prepared in current research using various proportions of Polysorbate 20 and maltodextrin as binary stabilizer mixtures through solvent-displacement technique. The effects of maltodextrin proportion in stabilizer mixture, on physicochemical characteristics of gained nanoemulsions, namely average particle size, polydispersity index (PDI), zeta potential, conductivity, in vitro antioxidant activity, in vitro cellular uptake and their rheological parameters were studied. The results show that using maltodextrin, as surface active biopolymer, together with Polysorbate 20, as small molecular stabilizer, could improve the characteristics of nanoemulsions considerably. The studied characteristics of all prepared shear-thinning (pseudo-plastic) nanoemulsions were well fitted to maltodextrin proportions via various polynomial models using regression statistical analysis. Thus, applying the surface active polysaccharides as stabilizer, in nanoemulsion formulations, and tuning its proportions to general used small molecular emulsifiers, can develop more desired functional lipid such as α-tocopherol nanoemulsions for various water-based food and pharmaceutical uses